Innovations in Enhanced and Improved Oil Recovery - New Advances (IntechOpen eBooks, 2024)
This book navigates the evolving landscape of Enhanced Oil Recovery (EOR) and Improved Oil Recovery (IOR), covering diverse topics such as lithological dynamics in CO2-EOR, the impact of asphaltene precipitation in WAG implementation, progress in CO2-EOR and storage technology, in situ foam generation for unconventional fractured reservoirs, electromagnetic radiation effects on heavy oil upgrading, advancements in hydraulic fracturing, in situ synthesis of nanoparticles, and operational insights in the Bakken Shale. This comprehensive volume serves as an indispensable resource for professionals and researchers in the ever-changing field of enhanced and improved oil recovery.